Modelling and Experimental Characterization of the Tensile Response of Ultra-High Performance Fibre-Reinforced Cementitious Composites - Abrishambaf, A (2018)
In this research, an experimental programme is developed to investigate the influence of fibre orientation on the tensile behaviour of UHPFRC from micro-mechanics to composite level. The micro-mechanical aspects of fibre reinforcement are analysed by performing single fibre pull-out test on the short fibres embedded in an ultra-high performance cementitious matrix. The influence of fibre embedded length (l(f)/2 and l(f)/4, l(f) being the fibre length) and fibre orientation (0 degrees, 30 degrees and 60 degrees) on the pull-out behaviour are appraised. At the composite level, uniaxial tensile tests (UTT) on UHPFRC specimens with varying fibre contents (1.5%, 2.3% and 3.0% volume fractions) and fibre orientation profiles (parallel to the loading direction, randomly oriented and perpendicular to the loading direction) are performed. The different fibre orientation profiles were obtained using a magnetic setup for orienting the fibres along a pre-defined direction during casting. An image analysis technique is employed to determine the fibre orientation angle distributions and other scalar fibre orientation indicators. The results of this experimental programme clearly evidence the effect of fibre orientation not only on the tensile strength, but also on the development of the hardening branch that is typical of this type of cementitious composites. Furthermore, a methodology to predict the tensile behaviour of the UHPFRC, both in the hardening and softening branches, is proposed taking into account fibre volume fraction, fibre orientation factor and fibre efficiency factor. The latter is determined from the fibre pull-out test. The model performance was validated against the UTT results and it is shown that the full tensile response can be reasonably predicted using the proposed meso-mechanical model.